Relationship between Resting Heart Rate, Blood Pressure and Pulse Pressure in Adolescents - Christofaro,Diego Giulliano Destro (2017)
Abstract Background: High resting heart rate is considered an important factor for increasing mortality chance in adults. However, it remains unclear whether the observed associations would remain after adjustment for confounders in adolescents. Objectives: To analyze the relationship between resting heart rate, blood pressure and pulse pressure in adolescents of both sexes. Methods: A cross-sectional study with 1231 adolescents (716 girls and 515 boys) aged 14-17 years. Heart rate, blood pressure and pulse pressure were evaluated using an oscillometric blood pressure device, validated for this population. Weight and height were measured with an electronic scale and a stadiometer, respectively, and waist circumference with a non-elastic tape. Multivariate analysis using linear regression investigated the relationship between resting heart rate and blood pressure and pulse pressure in boys and girls, controlling for general and abdominal obesity. Results: Higher resting heart rate values were observed in girls (80.1 ± 11.0 beats/min) compared to boys (75.9 ± 12.7 beats/min) (p ≤ 0.001). Resting heart rate was associated with systolic blood pressure in boys (Beta = 0.15 [0.04; 0.26]) and girls (Beta = 0.24 [0.16; 0.33]), with diastolic blood pressure in boys (Beta = 0.50 [0.37; 0.64]) and girls (Beta = 0.41 [0.30; 0.53]), and with pulse pressure in boys (Beta = -0.16 [-0.27; -0.04]). Conclusions: This study demonstrated a relationship between elevated resting heart rate and increased systolic and diastolic blood pressure in both sexes and pulse pressure in boys even after controlling for potential confounders, such as general and abdominal obesity.